2017
DOI: 10.1101/129221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amygdala input differentially influences prefrontal local field potential and single neuron encoding of reward-based decisions

Abstract: Reward-guided behaviors require functional interaction between amygdala, orbital (OFC), and medial (MFC) divisions of prefrontal cortex, but the neural mechanisms underlying these interactions are unclear. Here, we used a decoding approach to analyze local field potentials (LFPs) recorded from OFC and MFC of monkeys engaged in a stimulus-choice task, before and after excitotoxic amygdala lesions. Whereas OFC LFP responses were strongly modulated by the amount of reward associated with each stimulus, MFC respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 49 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Altogether, we found that many neurons across ventral frontal cortex represented the chosen flavor and probability of the outcomes that would follow a specific stimulus, further supporting the involvement of this part of frontal cortex in the valuation stage of decision making (Noonan et al, 2017;Murray and Rudebeck, 2018;Stoll and Rudebeck, 2023). Representations were, however, not uniform across subdivisions and were dissociable based on encoding and decoding approaches.…”
Section: Representation Of the Decision Variables During The Stimulus...mentioning
confidence: 65%
See 4 more Smart Citations
“…Altogether, we found that many neurons across ventral frontal cortex represented the chosen flavor and probability of the outcomes that would follow a specific stimulus, further supporting the involvement of this part of frontal cortex in the valuation stage of decision making (Noonan et al, 2017;Murray and Rudebeck, 2018;Stoll and Rudebeck, 2023). Representations were, however, not uniform across subdivisions and were dissociable based on encoding and decoding approaches.…”
Section: Representation Of the Decision Variables During The Stimulus...mentioning
confidence: 65%
“…Numerous prior reports have shown that neurons across frontal cortex often exhibit "mixed selectively" in that they code for multiple task features (Rigotti et al, 2013;Fusi et al, 2016). We and others previously reported that vlPFC and OFC neurons are highly likely to exhibit mixed selectivity while maintaining orthogonal representations of the factors important for valuation (for instance, (Wallis and Miller, 2003;Stoll and Rudebeck, 2023). To establish if there were any differences in the degree of mixed selectivity between subdivisions of ventral frontal cortex, we conducted a similar set of analyses here.…”
Section: Mixed Selectivity Within Ventral Frontal Cortexmentioning
confidence: 98%
See 3 more Smart Citations